Drivers of hypoxia variability in a shallow and eutrophicated semi-enclosed fjord. (March 2023) - Schourup-Kristensen, Vibe; Larsen, Janus; Maar, Marie
Abstract: Seasonal deoxygenation of coastal waters has been observed with increasing frequency around the world, with consequences for ecosystem functioning and continued benthic capacity to buffer hypoxia. Here, we present a hydrodynamical-ecological model study of the Limfjord in Denmark, an example of a semi-enclosed water body affected by recurring seasonal deoxygenation. Applying observations and model results, we show that water temperature, combined with wind strength and direction are the most important controllers of short-term interannual variability of bottom oxygen, while ventilation through episodic water inflow from the North Sea and local stratification create a spatial decoupling of deoxygenation. Nutrient load to the fjord drives sustained high biological productivity, but does not affect the interannual variability to the same degree. However, high biological turnover rates likely push the system closer towards a deoxygenated state, making the fjord more sensitive to future changes in temperature, wind and ventilation by reducing the buffer capacity of the sediments. Highlights: A coastal model including ecosystem is presented for the Limfjord, Denmark. Spatial variability of seasonal hypoxia mainly depends on stratification and inflow. Interannual variability of hypoxia controlled by wind strength and temperature.